Development and Validation of Fenofibrate in Bulk and Tablets using UV-Spectroscopy: An Anti-Hypercholesterolemic Agent - Boggula, Narender; Banothu, Bhadru; Devu, Satya Sireesha; Tadikonda, Rama Rao; Rapolu, Kiran (Asian Journal of Pharmaceutical Research and Development, 2024)
The spectrophotometry provides versatile techniques for analyse drug in multi component pharmaceutical formulation in presence of various interferences. Simple, accurate, sensitive, precise and rapid UV-Spectrophotometric methods have been developed for the estimation of fenofibrate in bulk and tablet dosage form formulation. To determine the absorption maximum, the drug fenofibrate were scanned in wavelength range of 200-400nm in spectra measurement mode using the double beam UV-Spectrophotometer, 290 nm was selected as a sampling wavelength in DMF as solvent. Beer’s limit was obeyed in the range of 2-10 µg/ml for fenofibrate. The correlation coefficient found to be satisfactory. Validation parameters such as its accuracy, linearity, precision, limit of detection (LOD), and limit of quantitation (LOQ) was studied for proposed method according to the ICH guidelines. Results of all parameters were found to be satisfactory. The proposed method can be used effectively for routine analysis and estimation of fenofibrate in bulk and dosage form. The result demonstrated that the proposed method is accurate, precise and reproducible.